2014
DOI: 10.18493/kmusekad.95564
|View full text |Cite
|
Sign up to set email alerts
|

60-72 Aylık Çocukların Türkçe Dil Kullanımı Düzeyleri Ve Etki Eden Faktörlerin İncelenmesi

Abstract: ÖzetBu araştırmanın temel amacı 60-72 aylık çocukların Türkçe dil kullanımı düzeylerini belirlemek ve etki eden faktörleri belirlemektir. Bu doğrultuda çocukların Türkçe dil kullanımı düzeylerini belirlemek için "Descoeudres Lügatçe Testinin Tamamlama İtemi" kullanılmıştır. Çalışma grubu 2010-2012 eğitim-öğretim yılında, Konya ili ilçelerinde bulunan, Milli Eğitim Bakanlığı'na bağlı bağımsız anaokulları ve anasınıflarında öğrenim gören ve görmeyen 60-72 aylık 292 çocuktan oluşmaktadır. Tarama modelinde olan ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
3
5
1
7
Order By: Relevance
“…According to the results of the study, the expressive language scores of the children did not differ significantly according to the age. This finding overlaps with some other research findings (Çat Şahin, 2008;Gürocak, 2007) but disagrees with others (Koçak, Ergin, Yalçın, 2014;Yıldırım, 2008). This result may be due to the characteristics of the children in the study group.…”
Section: Conclusion and Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…According to the results of the study, the expressive language scores of the children did not differ significantly according to the age. This finding overlaps with some other research findings (Çat Şahin, 2008;Gürocak, 2007) but disagrees with others (Koçak, Ergin, Yalçın, 2014;Yıldırım, 2008). This result may be due to the characteristics of the children in the study group.…”
Section: Conclusion and Discussioncontrasting
confidence: 52%
“…In the relevant literature it can be seen that differences in children's language skills favor both boys and girls. Özmermer (2008), Koçak, Ergin and Yalçın (2014) and Yıldırım, et al (2010) concluded that boys' language scores were higher than girls' scores. In contrast to these results, Çat Şahin (2008) and Erdoğan, Şimşek Bekir and Erdoğan Aras (2005) found that there was no significant difference in children's language scores according to gender.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Araştırmadan elde edilen bulgular doğrultusunda çocukların sosyal yetkinlik ve kızgınlık-saldırganlık davranışlarının kardeş sayısına göre anlamlı düzeyde farklılaşmadığı sonucunu elde etmişlerdir. Alanyazında kardeş sayısı değişkeninin çocukların sosyal becerileri üzerinde anlamlı farklılık oluşturmadığı sonuçlarına ulaşılan çalışmalar (Elibol Gültekin, 2008;Keçecioğlu, 2015) ve bir yandan dil gelişimi üzerinde anlamlı farklılık oluşturduğu sonuçlarının elde edildiği çalışmalar (Koçak, Ergin ve Yalçın, 2014) görülmektedir. Anne-baba tarafından çocuğa ayrılan nitelikli zamanın çocukların gelişimsel ilerlemeleri ve öğrenme süreçleri üzerinde olumlu etkileri bulunmaktadır.…”
Section: Discussionunclassified
“…In the research conducted by Ustun, Akman & Uyanık (2000) on children from a total of 143 different socioeconomic levels, 47 from the lower socioeconomic level, 46 from the middle socioeconomic level and 50 from the upper socioeconomic level, they tried to determine the maturity levels using a scale consisting of six sub-tests: word comprehension, sentences, general information, matching, numbers and copying, and there was a significant difference between the socioeconomic levels and school maturity. Koç ak, Ergin & Yalçın (2014) conducted a survey on 292 children in order to determine the factors that affect children's level of Turkish language use. The result of the study is that the variables of age, gender, educational background of the family and duration of pre-school education were significantly different in the language development levels of the children and that the number of siblings and birth order variables did not cause any significant difference.…”
mentioning
confidence: 99%